Correlation Between Serum 25-Hydroxyvitamin-D Levels and Disease Activity in Chronic Urticaria Patients at a Tertiary Referral Hospital in Jakarta, Indonesia - Sarah Mahri; Hanny Nilasari; Rinadewi Astriningrum; Windy K Budianti; Herqutanto (Journal of Pakistan Association of Dermatologists, 2022)
Background: The role of vitamin D in various chronic diseases is a matter of great interest. Vitamin D is thought to have an immunomodulatory effect and is associated with several allergic and autoimmune diseases, including chronic urticaria. Low vitamin D levels in patients with chronic urticaria have been reported and vitamin D supplementation has been shown to improve symptoms. However, data on the correlation between serum vitamin D levels and disease activity in chronic urticaria are still limited, especially in Indonesia. Objective: To analyze the correlation between vitamin D (25[OH]D) serum and disease activity in chronic urticaria patients. Methods: We performed an analytic-descriptive cross-sectional study. Disease activity, measured using the Urticaria Activity Acore 7 (UAS 7) questionnaire, and serum 25(OH)D levels were assessed in 30 chronic urticaria patients aged 18-59 years. Results: Mean UAS7 was 14.6, median duration of illness was 12 months, and the median serum 25(OH)D was 12.10 ng/mL. The majority of subjects had vitamin D deficiency (80%). There was no correlations between serum 25(OH)D levels and disease activity (r=0.151; p=0.425). However, a significant negative correlation was found in subjects with severe vitamin D deficiency (r=-0.916; p=0.001). There was also significant moderate correlation between disease activity and duration of illness (r=0.391; p=0.033). Conclusion: There was no correlation between serum 25(OH)D levels and disease activity, however there was a tendency of increasing disease activity in chronic urticaria patients with severe vitamin D deficiency.